PELAYANAN PUBLIK DAN KEADILAN SOSIAL - Khoiron Khoiron (Publisia: Jurnal Ilmu Administrasi Publik, 2017)
In the life of nation and state, society or people should be treated equally in various fields of life because the state is the result of social cooperation between people with each other, or among the children of the nation. In this case, the state is the government (umaro '), is the institution who most responsible for the basic services of its people. In the Islamic perspective, there is no clear system of governance, whether the governance is democratic or other systems. Islam only teaches how the country is managed with a trusteeship leader over his power. The value of ethics (morals), or morality, and justice and others is a guidebook as a trustful leader. Public service is the most fundamental basic need for citizens. Thus, the state must grant such this right to entire people without any discrimination and even provide an excellent service to the most disadvantaged communities in their social life. One of the great attitudes of the leader in Islamic scholar is Al-adalah or justice. Justice is so easy to pronounce, but it is difficult to achieve in every public policy. In qo'idah fiqihyah it is explained that "tasarruful imam ala al-roiyati, manutun bil al-maslahah", (the policy of a leader must base on the principle of greater utility to all his society). Thus, any policy in this regard is public service, issued by the state or government should consider the broadest utility principle (utilitarianism). Therefore, this paper will discuss about the social justice service from a normative-prescriptive perspective but also in the perspective of Islam as a religion of liberation. Islam is a religion of liberation from oppression, ignorance and complete religion. DOI: https://doi.org/10.26905/pjiap.v2i1.1418